Follow-up Actions on the Request for Explanation of Data and/or Information (SP2DK) as the Basis for Improving Tax Compliance (Case Study of Construction Companies in Medan City) - Junawan; Noviani; Noni Tambuwun; Shikin Aulia Azzahra (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the follow-up actions on the Request for Explanation of Data and/or Information (SP2DK) and its role in improving tax compliance in construction companies in Medan. The research background stems from findings by the Directorate General of Taxes (DJP) regarding discrepancies in the tax reporting data of companies, specifically for the 2022 Tax Year, where a company reported a business turnover of IDR 654,346,589 but did not make the final income tax payment (PPh Final), and the VAT return (SPT Masa PPN) was filed with free text entries. This situation led to the issuance of SP2DK as a clarification and preliminary guidance tool by the tax authorities. This research uses a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observations, and tax document reviews. Data analysis was conducted using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The study’s findings indicate that the company’s response to the SP2DK was through written explanations, face-to-face clarification with the Account Representative, corrections to SPT filings, and settlement of PPh Final payments. Factors influencing the follow-up actions include limited tax knowledge, perceptions of the risk of tax audits and penalties, the role of guidance from DJP, and the company's internal administrative readiness. The company also faced obstacles such as weak documentation, limited human resources with tax knowledge, and unintegrated financial record systems. This study concludes that SP2DK follow-up actions have positively impacted both formal and material tax compliance, as reflected in timely SPT submissions, alignment between taxes owed and actual transactions, and a shift towards more sustainable compliance behavior. Moreover, the study highlights that DJP’s role through persuasive communication and technical assistance is crucial in ensuring the success of SP2DK as a tax compliance improvement tool. This research is expected to be a reference for taxpayers, tax authorities, and future researchers in understanding the effectiveness of SP2DK as an instrument for improving tax compliance.